An increasing the growth of oil palm seedlings using the mulch and poc mixing method - Asmara Sari Nasution; Efi Said Ali (Jurnal Scientia, 2024)
In chemistry and agriculture, oil palm seedlings really need complete nutrients for their growth. So this research aims to determine the testing of several types of bamboo leaf mulch, palm leaf mulch and sugar cane leaf mulch and (POC) on the growth of oil palm (Elaeis Giuneensis Jacq) seedlings in the Pre Nursery and their interactions. The parameters observed were plant height (cm), number of leaves (strands), stem diameter (mm), wet weight (grams) and dry weight (grams). Based on the results of the research carried out, it can be seen that the test treatment of several types of mulch had no significant effect on plant height, number of leaves, stem diameter, wet weight and dry weight. The research results (POC) of banana peel did not have a significant effect on the number of leaves, stem diameter, wet weight and dry weight and had a significant effect on plant height. The interaction between several types of mulch and (POC) had a significant effect on the number of leaves and dry weight.